A business model typology for destination management organizations. Issue 6 (7th March 2018) - Reinhold, Stephan; Beritelli, Pietro; Grünig, Rouven
Abstract : Purpose: The need and legitimacy of destination management organizations (DMOs) are increasingly questioned. Still, the tourism literature provides little advice on how DMOs change and finance their activities for the benefit of their destination-given contextual change. This conceptual article aims to contribute to filling this gap. The authors do so by proposing a typology of business models for destination management organizations. Design/methodology/approach: With the help of typological reasoning, the authors develop a new framework of DMO business model ideal types. To this end, the authors draw on extant literature on business model typologies and identify key dimensions of DMO business models from the tourism literature. Findings: The challenges DMOs face, as discussed in the tourism literature, relate to both ends of their business model: On the one end, the value creation side, the perceived value of the activities they traditionally pursue has been declining; on the other end, the value capture side, revenue streams are less plentiful or attached to more extensive demands. On the basis of two dimensions, configurational complexity and perceived control, the authors identify four distinct ideal types of DMO business models: the destination factory, destination service center, value orchestrator and value enabler. Originality/value: The authors outline a "traditional" DMO business model that stands in contrast to existing DMO classifications and that relates DMO challenges to the business model concept. The typology provides an integrated description of how DMO business models may be positioned to create and capture value for the organization and the destination(s) it serves. The ideal types point to important interdependencies of specific business model design choices.